Management changes drive auditor switching in Indonesian companies: Pergantian manajemen mendorong pergantian auditor di perusahaan-perusahaan Indonesia - Ningtiyas, Dwi Ayu; Hariyanto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the influence of audit opinions, management changes, and company growth on auditor switching, with financial distress as a moderating variable, in transportation and infrastructure companies listed on the Indonesia Stock Exchange from 2018 to 2021. Using purposive sampling, 48 companies were selected, resulting in 192 data points analyzed using Partial Least Square (PLS). Results show that management changes significantly impact auditor switching, while audit opinions and company growth do not. Financial distress does not moderate these relationships. The findings underscore the importance of management changes in auditor decisions and suggest further research should explore additional factors and extend the study period for more comprehensive insights. Highlight: Management Changes: Significantly impact auditor switching. Audit Opinions and Growth: No significant effect on switching. Financial Distress: No moderating effect on studied relationships. Keyword: auditor switching, management changes, financial distress, audit opinions, company growth